Effect of agitation speed on morphological changes in Aspergillus niger hyphae in submerged fermentation system - Hanggara Sudrajat; Fernando Da Costa; Juan Manuel Serrano; Garcia Domenech (Indonesian Journal of Pharmacy, 2008)
The correlation between the agitation speed and the morphological changes occurred in the fungal hyphae during the production of tannase in a submerged fermentation system has been studied. Under optimal agitation speed, loose fungal pellet formation favored enzyme production. Based onthe SEM and TEM studies, it was found that there were significant correlations between the speed of agitation and the hyphal morphology including its internal structures, and the activity of enzyme production. This could be due to the excessive cell permeability related to abrasion by shear forces and also by oxygen limitation.Key words: Agitation speed, fungal hyphae, tannase, submerged, fermentation system.